"COMPLEMENT POLARITY" ON JUANDA AIRPORT TRAIN STATIONS IN SIDOARJO - Putra, Mohamad Ega; Winarto, Erwin Djuni (Border: Jurnal Arsitektur, 2019)
Juanda Airport is an international airport that is one of the infrastructure that is relied on by the Surabaya City government and the East Java provincial government to improve the economy of East Java. The increasing need for air transportation has made Juanda airport require development efforts to meet the needs of users from both locally and internationally while at the same time implementing the policies of the Government of the Republic of Indonesia regarding mass transportation. This study examines the importance of airport train stations presence as a form of transportation integration within the city. As the final result, this study submitted a design proposal with the theme chosen according to the conditions and context suitable for the Juanda airport train station. The airport train station proposal location is in the terminal 1 area of Juanda airport which is right in front of terminal 1. Based on the location, there are several problems, namely access to the station for passengers from terminal 2 and terminal 3 plans, vehicle movement patterns and passenger movement in airport train station operations, and the station's position is right in front of terminal 1 of the airport, this affects the appearance (identity) of joglo terminal 1. From the problems above the design proposal uses the theme "complement polarity" using the postmodern approach. Thus the Juanda airport train station is expected to be able to adjust to the system that has taken place at Juanda airport without disturbing each other.